The Dose-Dependent Effects of Multifunctional Enkephalin Analogs on the Protein Composition of Rat Spleen Lymphocytes, Cortex, and Hippocampus; Comparison with Changes Induced by Morphine - Ujcikova, Hana; Roubalova, Lenka; Lee, Yeon Sun; Slaninova, Jirina; Brejchova, Jana; Svoboda, Petr (Biomedicines, 2022)
This work aimed to test the effect of 7-day exposure of rats to multifunctional enkephalin analogs LYS739 and LYS744 at doses of 3 mg/kg and 10 mg/kg on the protein composition of rat spleen lymphocytes, brain cortex, and hippocampus. Alterations of proteome induced by LYS739 and LYS744 were compared with those elicited by morphine. The changes in rat proteome profiles were analyzed by label-free quantification (MaxLFQ). Proteomic analysis indicated that the treatment with 3 mg/kg of LYS744 caused significant alterations in protein expression levels in spleen lymphocytes (45), rat brain cortex (31), and hippocampus (42). The identified proteins were primarily involved in RNA processing and the regulation of cytoskeletal dynamics. In spleen lymphocytes, the administration of the higher 10 mg/kg dose of both enkephalin analogs caused major, extensive modifications in protein expression levels: LYS739 (119) and LYS744 (182). Among these changes, the number of proteins associated with immune responses and apoptotic processes was increased. LYS739 treatment resulted in the highest number of alterations in the rat brain cortex (152) and hippocampus (45). The altered proteins were functionally related to the regulation of transcription and cytoskeletal reorganization, which plays an essential role in neuronal plasticity. Administration with LYS744 did not increase the number of altered proteins in the brain cortex (26) and hippocampus (26). Our findings demonstrate that the effect of κ-OR full antagonism of LYS744 is opposite in the central nervous system and the peripheral region (spleen lymphocytes).
Keywords: proteomic analysis; chronic pain treatment; rat spleen lymphocytes; multifunctional enkephalin analogs; rat brain; label-free quantification; morphine